Bias Perilaku dalam Pengambilan Keputusan Keuangan UMKM: Studi Kasus Pendanaan Jangka Panjang Atwaajus Payaman Andonosari Kec. Tutur Kab. Pasuruan - Ach. Sadili Ridho; Ainur Rohmadiah Sherina Puteri; Ditta Noviana Putri; Muhammad Sofiyan Hadi; Nurul Izzahtul Islamiah (Ikatan Da'i Indonesia, 2025)
This study examines the influence of behavioral biases on long-term financing decisions in the ATWAJUUS PAYAMAN MSME, located in Desa Andonosari, Tutur District, Pasuruan. Primary data were collected through semi-structured interviews with the business founders, field observations, and operational documentation since 2015. A thematic analysis was conducted to identify decision-making patterns driven by psychological factors such as risk aversion, loss aversion, status quo bias, and herding behavior. The results indicate that the owners consistently rely on internal capital to avoid the psychological burden of interest and installments, reduce production volume when input prices surge, and maintain manual processes despite available automation options to empower local labor. The introduction of new product variants is also influenced by observing successful peers, even without formal market analysis. Limited financial literacy delays the adoption of digital financing, but positive responsiveness emerges following education and guidance. These findings underscore the need for training programs and access to low-interest micro-loans to support production capacity building and product innovation in rural MSMEs.